2013
DOI: 10.1080/09640568.2012.709467
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a carbon tax on economic growth and carbon dioxide emissions in Ireland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 26 publications
0
40
0
2
Order By: Relevance
“…Finally, Conefrey et al (2008) examine in the impacts of a carbon tax on emissions and economic growth, using the HERMES medium-term model of the Irish economy. Imposing a carbon tax of e20 per tonne CO 2 would, they find, result in a modest decline in emissions (between 2% and 2.5%).…”
Section: Related Literaturementioning
confidence: 99%
“…Finally, Conefrey et al (2008) examine in the impacts of a carbon tax on emissions and economic growth, using the HERMES medium-term model of the Irish economy. Imposing a carbon tax of e20 per tonne CO 2 would, they find, result in a modest decline in emissions (between 2% and 2.5%).…”
Section: Related Literaturementioning
confidence: 99%
“…A number of studies have suggested how the negative welfare impact can be minimised [Callan et al (2008); Conefrey et al (2012); Verde and Tol (2009)]. 2 to 2unc -0.9 0.1 -1.5 -0.4 -2.6 -0.9 0.4 0.1 …”
Section: Discussionmentioning
confidence: 99%
“…In that situation there is no additional tax revenue available to be recycled and policy responses, such as those discussed in Conefrey et al (2012) and di Cosmo and Hyland (2011), to offset negative welfare impacts will not be feasible. The scale of the welfare losses are difficult to quantify.…”
Section: Welfare Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic specification is similar to that set out in the original 1993 paper. Details of the latest version are set out in Conefrey et al, 2008. The model of output determination in the market services sector was published in an article in Bradley, FitzGerald and Kearney, 1991. It saw output in the market services sector as being predominantly driven by domestic demand.…”
Section: The Drivers Of Growth In the Tradable Sectormentioning
confidence: 99%